DOMENICO CRESTI (PASSIGNANO) AND THE FIRST ARTISTIC REPRESENTATION OF THE GALILEAN TELESCOPIC MOON - da Silva, Josie Agatha Parrilha; Neves, Marcos Cesar Danhoni (International Journal of Research -GRANTHAALAYAH, 2018)
This research reports the imagery representation of the Moon in the Virgin of the Immaculate Conception with Saints and Angels (1611) by Domenico Cresti (Passignano). Our goal is to defend this image as a telescopic representation of the Galilean Moon, that is, a cratered Moon as presented by Galileo Galilei in his work Sidereus nuncius (1610). Passignano was a friend of the artist Lodovico Cardi (Cigoli) who corresponded with Galileo and exchanged information on telescopic observations. This relationship between the artists and Galileo reinforces the possibility that the two painters had represented cratered the moons. The research consists of bibliographical and imaginary research and, at the end, the Moon of Passignano as the first representation of a Galilean Moon inside a Church.